Pengembangan Potensi Anak Pesisir melalui Pembelajaran Literasi Dasar dan Seni Kreatif Berbasis Komunitas - Hasmita Hasmita; Alfilnah Alfilnah; Sri Ayu; Sarmawan Muin; Idham Cholid; Muhammad Al Rajab; Fajar Kurniawan; Sultan Andilah; Tawakkal Tawakkal; Lisnawati Lisnawati; Efa Kelya Nasrun; Ira Nurmala (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
Children living in coastal areas face various challenges in developing their literacy and creative potential due to limited access to non-formal educational facilities and adequate learning resources. This condition results in low stimulation of reading, writing, communication, and creative expression skills from an early age. This community service activity aims to develop the potential of coastal children through basic literacy learning and community-based creative arts in Wawatu Village, North Moramo District, South Konawe Regency. The method applied is a community-based participatory approach with an experiential learning design, actively involving children in various educational activities such as shared reading, storytelling, drawing, coloring, singing, reading children’s poetry, and group-based educational games. Data were collected through participatory observation, brief interviews with children, parents, and community leaders, as well as simple questionnaires to assess participants’ responses and satisfaction levels. The results indicate high enthusiasm among the children, with most participants stating that they were very happy and happy to take part in the entire series of activities. The children became more active in interacting, more confident in expressing their opinions, and showed increased interest in reading and artistic activities. In addition, parents and community leaders expressed positive responses, as the program was considered to provide a contextual and meaningful alternative learning experience. This activity demonstrates that the integration of basic literacy learning and community-based creative arts is an effective approach to holistically developing the cognitive, social, and emotional abilities of coastal children while strengthening the role of the community in supporting children’s sustainable growth and development.